Rapid detection of Vibrio alginolyticus in seafood using the flgL gene and real-time polymerase chain reaction - Muktiningsih Nurjayadi; Gladys Indira Putri; Jefferson Lynford Declan; Ismaya Krisdawati; Dandy Akbar Juliansyah; Maharanianska Azzahra; Irvan Maulana; Irma Ratna Kartika; Fera Kurniadewi; Tiara Fahriza; Adinda Myra Amalia Putri; Ayu Berkahingrum; et al. (Acta Biochimica Indonesiana, 2024)
Background: Seafood is highly nutritious but poses health risks when contaminated with pathogenic bacteria like Vibrio alginolyticus, which causes food poisoning and can infect marine animals and humans.